2003
DOI: 10.1089/153623003772032844
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming in Inter-Species Embryonal Carcinoma–Somatic Cell Hybrids Induces Expression of Pluripotency and Differentiation Markers

Abstract: Somatic cell reprogramming holds great promise for the development of novel cellular therapeutics. A number of sources of reprogramming potential have been identified, including oocytes, embryonic germ (EG) cells and embryonic stem (ES) cells. However, each of these sources of reprogramming factors is problematic, since they are either not freely available or have special growth requirements. Embryonal carcinoma (EC) cells are another source of pluripotent cells that, unlike ES and EG cells, do not usually req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 58 publications
4
34
0
Order By: Relevance
“…7 In addition, embryonal carcinoma (EC) and embryonic germ (EG) cells have also been shown to contain reprogramming activities in fusion experiments. [13][14][15] Human fibroblasts have been successfully reprogrammed as well upon fusion with human ESC 8 or myeloid precursor cells. 16 The reprogramming activity of ESCs likely resides within the nuclear compartment because karyoplasts, but not cytoplasts, derived from these cells, can bring about reprogramming of somatic cells upon fusion.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, embryonal carcinoma (EC) and embryonic germ (EG) cells have also been shown to contain reprogramming activities in fusion experiments. [13][14][15] Human fibroblasts have been successfully reprogrammed as well upon fusion with human ESC 8 or myeloid precursor cells. 16 The reprogramming activity of ESCs likely resides within the nuclear compartment because karyoplasts, but not cytoplasts, derived from these cells, can bring about reprogramming of somatic cells upon fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mouse pluripotent stem cells can reprogram nuclei of human somatic cells into pluripotent state. This result indicates that reprogramming factors can cross-act through another species (29). Hence, reprogrammed fusion hybrid cells have been used for study of reprogramming mechanism.…”
Section: Cell Fusion-induced Reprogrammingmentioning
confidence: 99%
“…Following this initial study, many studies have shown that various somatic cells can be reprogrammed by fusing with pluripotent stem cell like ES, EG, or EC cells ( Fig. 1) (Cowan et al, 2005;Flasza et al, 2003;Matveeva et al, 1998;Shimazaki et al, 1993;Tada et al, 2003;Tada et al, 2001;Terada et al, 2002, Yu et al, 2006.…”
Section: Reprogramming Of Somatic Cells Using Cell-cell Fusion With Ementioning
confidence: 99%
“…Since EC cells share many of the key pluripotent characteristics with ES and EC cells can provide a readily amenable alternative source for reprogramming (Do et al, 2009a;Flasza et al, 2003;Mise et al, 1996). Moreover, mouse EC cells can reprogram human somatic cells into pluripotent state, indicating that reprogramming factors can cross-act through another species (Flasza et al, 2003).…”
Section: Reprogramming Of Somatic Cells Using Cell-cell Fusion With Ementioning
confidence: 99%